SIMULATION OF TRICKLE-BED REACTOR FOR CATALYTIC HYDRODEOXYGENATION (HDO) OF PALM OIL - Taufik, Affandry
Vegetable oil resources are the leading choice of renewable fuel sources. As a great exporter of palm oil and palm kernel oil, Indonesia needs to develop a process to convert vegetable oil to green fuel. Hydrodeoxygenation (HDO) is the best process to convert vegetable oil into green fuel. HDO of palm kernel oil has been studied in TRKK Laboratory, ITB. The catalyst shown good performance at certain condition then named PDO 130-1,2T. Performance study of PDO 130-1,2T has been simulated in LCO Treater UP IV Pertamina Balongan using RPKO (Refined Palm Kernel Oil) as the feed. The Yuwan’s kinetic equation can represent hydrodeoxigenation of palm kernel oil as a whole. ODE23 and PDEPE in Matlab 2015b used as a tools for one and two-dimensional simulation. The variables that used in this simulation are the ratio of hydrocarbon to triglycerides (HC/TG), WHSV (Weight Hourly Space Velocity), liquid phase inlet temperature (Tin), ratio hydrogen entering first bed to second bed (Qin/Qquench) and pressure. Increasing Tin, rasio HC/TG and pressure could maximized hydrogen solubility in liquid phase. Increasing ???????????? and pressure or lowering WHSV, ratio Qin/Qquench and ratio HC/TG led to increase conversion of triglycerides.